Prediction of austenite grain growth during hot rolling of 0.028% Nb steel - D., Priadi; R. A. M., Napitupulu; E. S., Siradj (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.